MODEL OF PROFESSIONAL TRAINING OF FUTURE MARITIME SPECIALISTS IN THE INFORMATIONAL AND TECHNOLOGICAL ENVIRONMENT (Journal of Information Technologies in Education (ITE), 2019)
The role of the maritime higher educational establishments is to prepare a future competent maritime specialist employee in such a way that he meets the requirements of the employer and is able to provide a qualitative professional activity on board. Therefore, professional competence of future maritime specialists as the ability to mobilize the knowledge and experience gained in a specific subject-professional activity is determined by knowledge, skills and abilities. Our research was aimed at modeling the professional training of future maritime professionals by an informational and technological environment. To the model of professional training of future maritime specialists in the information and technological educational environment we include the following blocks: motivational-targeted, theoretical-methodological, functional-content, procedural, criteriondiagnostic, effective and continuous-professional ones. Our study generalizes that the transition to a competency-based approach generates changes in the way of understanding education, when teachers, together with employers, must clearly define the ultimate goals of professional training for maritime professionals, goals should be formulated in terms of learning outcomes and expressed in terms of competencies, teaching is aimed at mastering students' finished algorithms of professional activity, without strict adherence to established rules or algorithms of activity. When assessing the competences of students, the system of assessing students’ academic achievement should take into account the monitoring and determination of the level of competence. The following integral components of the model are listed and described: organizational and pedagogical conditions, information and technological educational environment. As a result of our research, it was proved that the result of professional training of future specialists in the marine industry by means of information and technological educational environment positive dynamics of the professional competence level of future maritime specialists.
Keywords: informational and technological environment; maritime specialists; professional competence; professional training